Validity Validity Analysis of Joyful Learning Integrated Measurement E-Module for Student Knowledge and Creative Thinking - Kuntum Khaira Ummah; Asrizal Asrizal; Harman Amir; Dea Stivani Suherman (Physics Learning and Education, 2026)
This study aims to analyze the validity of the development of digital teaching materials for measurement topics that integrate a joyful learning approach to facilitate students' knowledge and creative thinking skills. The applied method is Research and Development (R&D) based on the Hannafin and Peck model, which includes the analysis, design, and development stages. The validity of the teaching materials was assessed by three validators through aspects of material substance, learning design, visual communication, software utilization, integration of joyful learning, and knowledge and creative thinking skills. The results showed that the teaching materials were classified as very valid with an average score of 0.88. Specifically, the validity scores reached 0.84 for material substance, 0.93 for learning design, 0.90 for visual communication, 0.92 for software utilization, 0.89 for integration of joyful learning, and 0.82 for knowledge and creative thinking skills. These findings confirm the product's suitability to scientific standards, the Independent Curriculum, and 21st-century learning needs. The integration of digital technologies such as Canva, Liveworksheet, and Google Forms improves the quality of the teaching materials, resulting in a fun, interactive, and adaptive learning experience. Thus, this research contributes significantly to the development of innovative, valid, and effective physics learning media in strengthening students' knowledge and creative thinking skills.